2008
DOI: 10.1016/j.mce.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of facilitative glucose transporters (GLUTs) in human thyroid carcinoma cell lines and primary tumors

Abstract: Expression analysis of facilitative glucose transporters (GLUTs) in human thyroid carcinoma cell lines and primary tumors, Molecular and Cellular Endocrinology (2007), doi:10.1016/j.mce.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 28 publications
5
28
0
2
Order By: Relevance
“…Ninety-five percent of human follicular carcinomas are deficient for GLUT-1 messenger RNA (23). This observation is not completely unexpected and also agrees with results obtained by Ciampi et al, who reported an overexpression of GLUT-3 in other well-differentiated follicular thyroid carcinoma cell lines (24).…”
Section: Discussionsupporting
confidence: 91%
“…Ninety-five percent of human follicular carcinomas are deficient for GLUT-1 messenger RNA (23). This observation is not completely unexpected and also agrees with results obtained by Ciampi et al, who reported an overexpression of GLUT-3 in other well-differentiated follicular thyroid carcinoma cell lines (24).…”
Section: Discussionsupporting
confidence: 91%
“…Thyroid cancer cells also show a high rate of glycolysis (Andrade et al 2012). Immunohistochemical studies have shown that enhanced glucose uptake in cancer cells correlates with over-expression of GLUTs, in most cases GLUT1 (Haber et al 1997, Ciampi et al 2008. Herein, we show that the oncosuppressor PTEN plays a dominant role in the membrane expression of GLUT1 and glucose uptake in thyroid cancer cells.…”
Section: Discussionmentioning
confidence: 62%
“…However, the expression of GLUT3 (SLC2A3) can be observed in DTCs (Ciampi et al 2008), and correlations between GLUT3, GLUT4 (SLC2A4), and SUV were significant in thyroid cancer (Kaida et al 2011). Therefore, FDG uptake may be determined by the expression of GLUT3 and GLUT4 (Kaida et al 2011).…”
Section: Factors Associated With the Fdg Avidity Of Dtcsmentioning
confidence: 99%